Analytical applications of ion exchangers - Inczedy, J. (Pergamon Press, 1966)
Analytical Applications of Ion Exchangers presents the laboratory use of ion-exchange resins. This book discusses the development in the analytical application of ion exchangers. Organized into 10 chapters, this book begins with an overview of the history and significance of ion exchangers for technical purposes. This text then describes the properties of ion exchangers, which are large molecular water-insoluble polyelectrolytes having a cross-linked structure that contains ionic groups. Other chapters consider the theories concerning the operation of ion-exchange resins and investigate the pr.